2017
DOI: 10.1111/joic.12470
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization of native superficial femoral artery chronic total occlusion after failed femoropopliteal bypass in patients with critical limb ischemia

Abstract: Objectives This study aimed to examine the outcomes of endovascular recanalization for native superficial femoral artery (SFA) chronic total occlusion (CTO) in patients with critical limb ischemia (CLI) after femoropopliteal bypass failure with limited surgical revascularization options. Background Endovascular recanalization of native artery occlusions has been recently used as a new alternative for threatened limbs after bypass graft occlusion. The feasibility and efficacy has not been widely reported. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
7
2
1
Order By: Relevance
“…Another important nding is that a lesion length ≥ 30 cm and a TASC II D lesion are predictors of primary patency loss. This nding is in contrast with one of the few previously published reports on the endovascular recanalization of the native SFA CTOs in patients with CLI after failed femoropopliteal bypass (Li Z et al, 2018), whose regression analysis had not shown signi cant in uence of a lesion length > 20 cm and a TASC II D lesion on the primary patency loss, but it's in agreement with the historical and contemporary vascular literature on primary endovascular therapy for lower limb lesions (Jørgensen B et al, 1991;Iida O et al, 2014). The below-knee popliteal artery bypass target heralds the presence of a more extensive TASC II D disease of the native SFA, strongly associated with a higher rate of restenosis after a percutaneous intervention ).…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…Another important nding is that a lesion length ≥ 30 cm and a TASC II D lesion are predictors of primary patency loss. This nding is in contrast with one of the few previously published reports on the endovascular recanalization of the native SFA CTOs in patients with CLI after failed femoropopliteal bypass (Li Z et al, 2018), whose regression analysis had not shown signi cant in uence of a lesion length > 20 cm and a TASC II D lesion on the primary patency loss, but it's in agreement with the historical and contemporary vascular literature on primary endovascular therapy for lower limb lesions (Jørgensen B et al, 1991;Iida O et al, 2014). The below-knee popliteal artery bypass target heralds the presence of a more extensive TASC II D disease of the native SFA, strongly associated with a higher rate of restenosis after a percutaneous intervention ).…”
Section: Resultscontrasting
confidence: 92%
“…Hence, the idea to recanalize the native SFA chronic total occlusions, in patients with critical limb ischemia (CLI) and femoro-popliteal bypass failure, has been born, limited to those patients un t for surgery or refusing surgical reconstruction. Data regarding this approach in femoro-popliteal bypass failure are limited to few case-series studies (Li Z et al, 2018;Gandini R et al, 2009;Davies MG et al, 2017), so the need of new studies should be emphasized in order to better understand long-term outcomes of this option compared to secondary bypass surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the idea to recanalize the native SFA chronic total occlusions has been born in patients with critical limb ischemia (CLI) and femoro-popliteal bypass failure, limited to those cases unfit for surgery or refusing surgical reconstruction. Data regarding this approach in femoro-popliteal bypass failure are limited to few case-series studies (Li et al 2018 ; Gandini et al 2009 ; Davies et al 2017 ), so the need for new studies should be emphasized to better understand long-term outcomes of this option compared to secondary bypass surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Субинтимальная реканализация артерий представляет собой еще одну опцию для эндоваскулярной реваскуляризации конечности [17][18][19][20]. Есть информация о том, что после тромбоза бедренно-подколенно-дистальных шунтов возможно успешное спасение конечности за счет подобных вмешательств [21][22][23][24][25][26]. Тем не менее, насколько нам известно, работ по комбинации этой методики с открытыми вмешательствами пока не было.…”
Section: Discussionunclassified